"WILLAM WORDSWORTH" AND HIS CONTRIBUTION TO ENGLISH POETRY: ANALYSIS OF LUCY POEMS, THE PRELUDE AND LYRICAL BALLADS - Raghuvanshi, Neelu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
“Willam Wordsworth” is known as one of the most efficient poets of “English literature” whose contributions cannot be understated. This paper will explore the contributions made by "Willam Wordsworth" in English Poetry. Three famous works by "Willam Wordsworth" will be analysed here which includes “Lucy poems, The Prelude and Lyrical Ballads”. The research will use a comparative, thematic and content analysis process to analyse the impact "Willam Wordsworth" had on nature. The Prelude shoes the personal growth and opportunities for self-exploration of "Willam Wordsworth" while Lucy Poems explored the themes of “beauty, loss, and mortality”. Lyrical Ballads has focused on simplifying language and also making poetry accessible for the masses. The research has found that there are common motifs in all the poems which are the “transformative power of nature, the transience of life, and human introspection”. This shows the cohesive poetic vision of Wordsworth which was important in establishing Romanticism.